Stakeholder Requirements for - Coetzee, Tjaart Petrus (My University, 2011)
Over the course of the 20th century, corporate social and environmental reporting (CSR), also referred to as sustainability reporting, has increased dramatically in its extent and importance. The research study documents the relative importance of aspects of corporate social and environmental reporting to stakeholders. It also documents the views that various stakeholder groups hold regarding the effectiveness of reporting. These views were obtained by following a process of focused interviews with senior executives and managers of organisations representing eight different stakeholder groups. The main findings that emerged reveal that stakeholders such as shareholders, financial analysts and providers of finance, attach a high level of importance to the economic performance of companies. However, they indicated that they have a very limited interest in the social and environmental performance of companies and make very little use of the information contained in CSR. Employees, customers, communities, NGOs and regulators have a high interest in the social and environmental performance and reporting, although they realise that sound economic performance is essential for the continuing existence of companies. All stakeholder groups indicated that engagement by companies regarding CSR is very limited and that there is a perception amongst stakeholders that reporting is positively biased. CSR in South Africa is not meeting the requirements of many stakeholder groups. A structured process of proactive engagement with stakeholders is required to improve the relevance of CSR. Such a process of engagement could, over time, revise the perception that CSR is not an accurate reflection of company performance.
MBA - WBS
Keywords: Corporate social reporting; Corporate environmental reporting